Analysis of the social structure of bottlenose dolphins (Tursiops truncatus) in São Miguel Island, Azores - Pereira, Andreia Filipa Figueiredo (2021)
Studying social structure is a valuable technique to reveal the factors driving population processes, to understand the evolution of cooperation, the transmission of diseases, and patterns of social learning. Therefore, understanding social relationships between individuals and the differences in habitat use among social groups is critically important to ensure species management and conservation. Bottlenose dolphins are one of the most sighted cetacean species in the Azores archipelago. They are present year-round, frequently encountered close to the islands, as well as in offshore waters. This study aimed to update the existing bottlenose dolphin photo-identification catalogue of São Miguel (2014-2019) with photos taken in 2008, 2010, 2012 and 2020 on board Futurismo’s whale watching vessels and analyse the social structure of the identified individuals. There were added to the catalogue 184 new individuals, having now the current catalogue of bottlenose dolphins in São Miguel, a total of 689 individuals identified. The social analyses have shown that associations between bottlenose dolphins identified in São Miguel are very dynamic and social bonds can be very flexible. The low association coefficients between pairs of individuals and consequently the low average coefficient of association for the population is in concordance with the typical fission-fusion society that characterizes this dolphin species. However, the higher association index of some individuals, suggest some long-term relationships. Some degree of structuring within the population of bottlenose dolphins in São Miguel with five groups identified was detected. Resident dolphins were sighted with migrants, individuals with more significant scale movements, contributing to an increase in genetic variability in oceanic dolphin communities. This study highlights the importance of long-term data series obtained from opportunistic platforms in Azores and provides a significant contribution to assess baselines conditions of the population and develop management strategies.